Central European forest floor bryophytes: Richness, species composition, coexistence and diagnostic significance across environmental gradients of forest habitats. (June 2022) - Stefańska-Krzaczek, Ewa; Swacha, Grzegorz; Żarnowiec, Jan; Raduła, Małgorzata W.; Kącki, Zygmunt; Staniaszek-Kik, Monika
Graphical abstract: Highlights: Bryophyte species number, cover and composition depend on environmental variables. Bryophyte species are indicators of forest types and tend to coexist. Groups of coexisting species respond to environmental gradients. Moist forests are hotspots of the diversity of forest floor bryophytes. Databases of vegetation-plots provide limited data on bryophyte ecology. Abstract: Bryophytes are good indicators of habitat conditions and show associations with different types of forests. In this study we assessed the diversity and distribution of forest floor bryophytes across a wide gradient of Central European forests using vegetation records from the Polish Vegetation Database (PVD). We identified forest types using the Habitat Classification of the European Nature Information System (EUNIS) – the main comprehensive pan-European hierarchical classification of habitats. Based on 9258 plots containing bryophyte species and representing 20 forest types, we assessed the species number and cover, species composition of the bryophyte layer, species tendency for coexistence, and bryophyte diagnostic value for forest types. We explained the observed trends by environmental variables and bryophyte species traits to understand how bryophytes function in forest habitats. Bryophyte species number and cover were high in forest types on moist sites, both with deciduous and coniferous tree stands. The richness and abundance of bryophyte species, as well as the species composition of the bryophyte layer depended mainly on substrate moisture, fertility and pH, as well as on the percentage cover of coniferous and deciduous tree species in the stand. Species traits which responded to environmental factors were, first of all, requirements for substrate moisture, fertility and pH. Bryophytes of closed forests and short-lived shuttle species preferred deciduous stands, while bryophytes occurring in forests as well as on open land and perennial species were associated with coniferous stands. Bryophyte species showed a clear preference for forest types, but their fidelity was usually not high. Based on the fidelity of species, we also identified 10 groups of coexisting species which were also indicators of forest types and were dependent on environmental variables. Forest floor bryophytes respond to environmental gradients by species number, cover and composition, and they play a diagnostic role in forest types. Our research shows the importance of databases in learning about bryophyte ecology. However, the use of vegetation data has some limitations.